Evaluation of coverage of mass drug administration programme conducted in Nalgonda district of Telangana state - Ganapa, Praveena; Jothula, Kishore Y.; Guthi, Vishweswara Rao; Abhishek, P.; Jyothi, V.; Sreeharshika, D.; Reddy, Pramodh (International Journal Of Community Medicine And Public Health, 2018)
Background: Lymphatic filariasis has been a major public health problem in India. Government of India during 2004 initiated Mass Drug Administration (MDA) with annual single dose of DEC tablets to all the population living at the risk of filariasis. Nalgonda is endemic district where MDA programme is undertaken every year to eliminate lymphatic filariasis. The present study was undertaken to evaluate the coverage and compliance rates of the MDA programme conducted during January 2018. Methods: The guidelines of National Vector Borne Disease Control Programme (NVBDCP) were used to select a total of 129 households from four clusters (three rural and one urban). Each household was visited by a team and data was recorded on pre-structured questionnaire available in operational guidelines manual of NVBDCP. Data analyzed by SPSS version 22. Results: Total of 129 households were included in the study, Among the 523 study population, only 494 were eligible population to receive MDA. Current study shows that coverage rate was 79.84% and compliance rate was 84.6%. Fear of side effects was most common reason for noncompliance. Conclusions: Efforts should be made to improve coverage rates by involving more human resources, supervision and incentives. Though compliance rates were higher than required there is need to maintain these rates by IEC activities and community participation.